Assessment of Formation of the Doctor’s Priority Personality Orientation Towards Professional Accomplishments - D. P. Derbenev; R. V. Maiorov (Здоровье мегаполиса, 2023)
Background. Numerous psychological traits may contribute to the success of a doctor's career, with the priority orientation of an individual towards qualitative and effective solving of professional tasks being among the most important factors.Purpose. The purpose of the study was to determine the prevalence and to study the determinants of priority orientation of an individual towards qualitative and effective solving of professional tasks among internal medicine physicians of the Tver region.Materials and methods. This medical and social study was conducted as a selective single-stage study based on a set of methodological procedures and techniques related to sociological, psychodiagnostic and statistical methods. A representative sample (p < 0,05) included 597 internal medicine physicians working in medical organizations in the Tver region.Results. Authors assessed the incidence of the priority orientation towards qualitative and effective solving of professional tasks among internal medicine physicians in general and in certain gender and age groups. We identified 16 significant (p < 0,05) medical, social and psychological factors influencing the formation of this priority orientation of internal medicine physicians’ personality, as well as their significance.Conclusions1. The prevalence of the priority orientation was observed among 32,9% of internal medicine physicians in the Tver region. Statistical data showed that in men the indicators were significantly higher compared to women of all age.2. Medical and social factors of professional environment supported by psychological determinants of professional motivational and value plan greatly influence the shaping the priority orientation of an individual towards qualitative and effective solving of professional tasks among internal medicine physicians.